2013
DOI: 10.4028/www.scientific.net/msf.740-742.477
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Level-Transient Spectroscopy Characterization of Mobility-Limiting Traps in SiO<sub>2</sub>/SiC Interfaces on C-Face 4H-SiC

Abstract: Constant-capacitance deep-level-transient spectroscopy (CCDLTS) characterization of traps (or states) in SiO2/SiC interfaces on the C-face was carried out to clarify the cause of low-channel mobility of SiC MOSFETs. CCDLTS measurements showed that the interface-state density (Dit) near the conduction band of SiO2/SiC interfaces fabricated using N2O oxidation was much higher than that of SiO2/SiC interfaces fabricated using wet oxidation. The high density of interface states near the conduction band is likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The obtained result is similar to constant-capacitance deep level transient spectroscopy data which has a similar measurement concept. Consequently, the low energy peak may be positioned at 0.16eV [23]. Figure 7.…”
Section: Distributionmentioning
confidence: 96%
“…The obtained result is similar to constant-capacitance deep level transient spectroscopy data which has a similar measurement concept. Consequently, the low energy peak may be positioned at 0.16eV [23]. Figure 7.…”
Section: Distributionmentioning
confidence: 96%
“…First, we examined the CCDLTS spectra of MOS capacitors on C-face to clarify the cause of the low mobility of the oxynitrided interface [16]. Figure 1 (a) shows the comparison of the CCDLTS spectra between a DWHC sample, the interface of which exhibits a high mobility, and an NHC sample, the interface of which exhibits relatively low mobility.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The authors reported that the D it close to the conduction band in SiC/SiO 2 interfaces fabricated using oxynitridation was much higher than that of SiC/SiO 2 interfaces fabricated using wet oxidation on C-face by using constant-capacitance deep-level transient spectroscopy (CCDLTS) characterization. [16]. They concluded that the low mobility in SiC/SiO 2 interfaces oxidized in a N 2 O atmosphere on C-face should be caused by trapping electrons in the high density of the traps close to the conduction band.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias adjustment resulted in feedback, which is equivalent to constantcapacitance DLTS (CCDLTS). [14][15][16][17][18] We examined the energy distribution of the interface-state density (D it ) near the conduction-band-edge energy (E c ) in n-type MOS capacitors by the DLTS method. The DLTS method can yield measurements from shallow states to deep states within a single temperature sweep, and enabling us to define the time constant and depth profile of the states.…”
Section: Methodsmentioning
confidence: 99%